Ownership changes of Japanese affiliates in China: lessons from the perspective of growth options exercising - Hongru Liu; Qiaoying Zhu (Cogent Business & Management, 2023)
Based on Real Options Theory and taking the perspective of growth options exercising, as well as Tobit model, this paper explores how Japanese enterprises adjust ownership structures in their affiliates as a portfolio in China. Empirical results show that: both demand uncertainty and industry growth opportunity in China enhance Japanese enterprises' ownership expansion in their affiliates as a real option portfolio; Industry competition and capability to control and coordinate the affiliates strengthen the roles of uncertainty and industry growth opportunity play in enhancing Japanese enterprises' ownership expansion within these affiliates as a portfolio. This paper enriches studies on growth options exercising and illustrates that the logic for real options establishing should not be simply and directly transplanted to real options exercising indiscriminately. Conclusions derived from this paper are of great significance for MNEs' growth option exercising by adjusting ownership structures in their affiliates as a portfolio within a host country according to changes in the focal host market.
Keywords: 650; competition; control and coordination capability; growth opportunity; ownership expansion; Uncertainty